The case of the surprise call - Metz, Melinda (Scholastic New York, 1999)
When Mary-Kate and Ashley get to their great-grandmother's detective clubhouse, they discover that someone had broken in. Was it the singing dragon, the giant bunny, or the mysterious stranger that kept calling them?